Neutralizing Monoclonal Antibodies That Target the Spike Receptor Binding Domain Confer Fc Receptor-Independent Protection against SARS-CoV-2 Infection in Syrian Hamsters - Wen Su (American Society for Microbiology, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein is the main target for neutralizing antibodies. These antibodies can be elicited through immunization or passively transferred as therapeutics in the form of convalescent-phase sera or monoclonal antibodies (MAbs).